(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In today’s technology-driven world, digital transformation has become a compelling trend that is reshaping businesses and industries. This article explores the evolving landscape of digital technology and its impact on organizations. It delves into the key drivers behind digital transformation, such as changing consumer expectations, disruptive technologies, and the need for agility and innovation. The article also discusses the challenges and opportunities that arise from digital transformation, and provides insights on how organizations can navigate this dynamic landscape to stay competitive and relevant in the digital age. Overall, this article aims to provide a comprehensive overview of the compelling trend of digital transformation and its implications for businesses.